Institutional Evaluation in Basic Education Schools: a participation-oriented approach - Dalben, Adilson (2010)
The present work is a synthesis of my Master’s Degree dissertation in which I tried to identify the factors that have influenced the implementation of Participatory Institutional Evaluation in a public primary school of the periphery of Campinas, a Brazilian municipality in the state of Sao Paulo. Based on the concept of negotiated quality, the enactment of the institutional evaluation model proposed required the constitution of an Evaluation Commission by representatives of diverse actors of the school community. The research consisted of a qualitative case study, using data collected from October 2005 to December 2006, when I entered the school environment in order to support the school to develop its evaluation process. Four categories of analysis were constructed to reflect on the school political pedagogical project, the educational culture of the school principal, the nuances of participation and the potentialities of participative institutional evaluation. The results acknowledge the potential of participative institutional evaluation as a means for democratic management and for technical and political capacity building at the school level aimed at overcoming problems faced by the school.